2018
DOI: 10.1002/ppap.201800067
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization of inulin in the highly reactive gas phase of a non thermal plasma at atmospheric pressure

Abstract: The interest of fructose production arises from its sweetening character used in application such as food and pharmaceutic industries. Fructose formation is achieved by the short treatment of inulin by non thermal plasma at atmospheric pressure, under air, using a dielectric barrier discharge (DBD) configuration. Promising results were observed as a total conversion of inulin was achieved within 10 min of treatment (18 kV, 2 kHz), without the addition of solvent, nor catalyst and at room temperature. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The stretching vibration of the existence of νC-H and the broad band at 1647 cm −1 in all EPSs analyzed specify residual water presence [48,51]. The appearance of a δC-O-H bending vibration at 1380-1340 cm −1 was also observed and could serve as a feature of the fructose oligomers and polymers [52].…”
Section: Characterization Of Bacterial Levan Biosynthesized By Strept...mentioning
confidence: 72%
“…The stretching vibration of the existence of νC-H and the broad band at 1647 cm −1 in all EPSs analyzed specify residual water presence [48,51]. The appearance of a δC-O-H bending vibration at 1380-1340 cm −1 was also observed and could serve as a feature of the fructose oligomers and polymers [52].…”
Section: Characterization Of Bacterial Levan Biosynthesized By Strept...mentioning
confidence: 72%
“…Accordingly, many efforts have been given to the development of pretreatment methods allowing partial hydrolysis of resistant cellulose (ball‐milling, dissolution of cellulose in ionic liquids) 6–8 . Pioneer investigations reported by some of the present authors showed a significant enhancement of hydrolysis to valuable glucans could be obtained by non‐thermal atmospheric plasma (NTAP) treatment 3,9–12 . Moreover, NTAP methodology allows to avoid laborious purification procedures, as no catalyst or solvent is necessary.…”
Section: Introductionmentioning
confidence: 96%
“…[6][7][8] Pioneer investigations reported by some of the present authors showed a significant enhancement of hydrolysis to valuable glucans could be obtained by non-thermal atmospheric plasma (NTAP) treatment. 3,[9][10][11][12] Moreover, NTAP methodology allows to avoid laborious purification procedures, as no catalyst or solvent is necessary.…”
Section: Introductionmentioning
confidence: 99%